2023
DOI: 10.3390/nu15030768
|View full text |Cite
|
Sign up to set email alerts
|

Association between Edinburgh Postnatal Depression Scale and Serum Levels of Ketone Bodies and Vitamin D, Thyroid Function, and Iron Metabolism

Abstract: Suicide due to postpartum depression is the most common perinatal-related death and is a social concern in Japan. Nutritional deficiencies during pregnancy may contribute to postpartum depression; therefore, we investigated the relationship between postpartum depression and nutritional status during pregnancy and postpartum. We focused specifically on ketone bodies because they are known to protect brain cells. The relationship between the Edinburgh Postnatal Depression Scale (EPDS) scores and the serum levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The visualizations completed for the top four continuous covariates were concordant with current literature: there is strong epidemiological evidence that good diet is associated with decreased risk of depression 22 . Many authors have noted statistically significant associations between Vitamin B6, Dietary Fiber, Potassium Intake, Vitamin E, Low Fat and Low Cholesterol Diet, Copper, Caffeine, Lutein Zeaxanthin, Phosphorous, Food Folate, Folate, Vitamin K, Iron, Theobromine, Total Choline, Magnesium, Sodium, Grams of Protein, Vitamin B12, Fiber, and Zinc similarly to our study 38–43 . Since visualizations for risk factors match literature relationships, we have increased confidence that the machine learning model is able to capture the actual physiological relationships of these covariates 44–51 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The visualizations completed for the top four continuous covariates were concordant with current literature: there is strong epidemiological evidence that good diet is associated with decreased risk of depression 22 . Many authors have noted statistically significant associations between Vitamin B6, Dietary Fiber, Potassium Intake, Vitamin E, Low Fat and Low Cholesterol Diet, Copper, Caffeine, Lutein Zeaxanthin, Phosphorous, Food Folate, Folate, Vitamin K, Iron, Theobromine, Total Choline, Magnesium, Sodium, Grams of Protein, Vitamin B12, Fiber, and Zinc similarly to our study 38–43 . Since visualizations for risk factors match literature relationships, we have increased confidence that the machine learning model is able to capture the actual physiological relationships of these covariates 44–51 .…”
Section: Discussionsupporting
confidence: 80%
“…22 Many authors have noted statistically significant associations between Vitamin B6, Dietary Fiber, Potassium Intake, Vitamin E, Low Fat and Low Cholesterol Diet, Copper, Caffeine, Lutein Zeaxanthin, Phosphorous, Food Folate, Folate, Vitamin K, Iron, Theobromine, Total Choline, Magnesium, Sodium, Grams of Protein, Vitamin B12, Fiber, and Zinc similarly to our study. [38][39][40][41][42][43] Since visualizations for risk factors match literature relationships, we have increased confidence that the machine learning model is able to capture the actual physiological relationships of these covariates. [44][45][46][47][48][49][50][51] These transparent machine-learning tools allow for increased confidence that these algorithms are picking up true signal within these covariates to predict the presence of depression rather than just replicating potential biases stemming from systemic data-quality errors that are present within the data set.…”
Section: Resultsmentioning
confidence: 99%
“…The results reveal the absence of a causal relationship between genetically determined variations in 25(OH)D levels and the risk of PPD. While a majority of available observational studies, often employing cross-sectional or case-control designs, have reported there exists an inverse correlation between the levels of 25(OH)D and postpartum depression [ 22 , 23 ], some studies have failed to establish a significant association between 25(OH)D levels and the occurrence or development of PPD [ 24 , 25 ]. Indeed, the true nature of the relationship between PPD and 25(OH)D remains unclear due to confounding factors and potential reverse causation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, obtaining EDPS scores earlier than six months may also provide further evidence of a possible correlation. Additionally, there are other studies that fail to associate varying peripartum TSH levels with PPD, thus raising considerable doubt regarding its use as a marker [ 28 , 29 ]. When considering clinical application, it is also important to consider the logistical difficulties of obtaining serum TSH levels during the intense process of labor.…”
Section: Reviewmentioning
confidence: 99%
“…Several studies illustrated the association between thyroid hormones and PMD. Elevated levels of TSH during labor are significantly associated with an increased risk of PPD at 6 months postpartum [ 27 ], however, other studies cast doubt on this association [ 28 , 29 ]. Low levels of total and free T4 in the third trimester were also correlated with PPD in a prospective cohort study conducted by Pedersen et al [ 26 ].…”
Section: Reviewmentioning
confidence: 99%